Nepali ESL/EFL Student Translators' Manipulation of Sentences at the Textual Level - Adhikari, Bal Ram (Nepalese Linguistics, 2023)
This paper analyzes English translations of Nepali short stories carried out by Nepali ESL/EFL student translators and examines the translators' manipulation of sentences across boundaries. The study adopted a product-oriented framework with a production task to elicit translation from 30 university translation students.  The data were analyzed descriptively and discussed under three themes: sentence splitting, sentence joining and sentence-structure preserving. Findings show translators' tendency to preserve source-text sentence boundaries in target texts, with the minimum use of sentence-splitting and sentence-merging strategies to bring about shifts across sentence boundaries.